Câncer Infantil: lugares simbólicos e imaginários no laço pais/filhos. - Barbosa, Kílvia Queiroz (2008)
We propose in this dissertation to understand the childhood cancer linked to the subjective constitution process, taking as a reference the psychoanalytic study of somatic symptoms in babies and small children from the symbolic and imaginary places that children have on parent’s desire. We address this issue articulating the process of the subject construction with the drive work, where the mother – as the Other - is of great importance for its function of excitement-shielding and, therefore, as an organizer of the drive circuit. It is, therefore, on the time of subjective constitution that we believe we can find the key to understanding the somatic symptoms, since it is in early childhood that the imaginary and symbolic body is formed in this double with the anatomical body. In this study, we used as the theoretical framework the psychoanalytic psychosomatic and Assoun´s texts, both based in Freudian metapsychology. The first one gives us an understanding about the formation of somatic symptoms from the primary relationships the child has with his parents. The second one, deals with somatic symptoms from a drive unmerge located in the origin of the I-body, forming the link with the Other. This is a qualitative research, with semi-structured interviews with six parents who were accompanying their children during hospitalization time in a known public hospital in Fortaleza-CE. The data were submitted to the method of content analysis, which center themes were maternal function and somatic symptoms. The analysis of these issues has shown us that the quality of the parents/children link suffer the effects of maternal desire that brings, itself, the mark of the inherent ambivalence in this relationship, through the psychic conflict, that when is not resolved in terms of symbolic development, falls on the body (of the child) as an affiliation, the mark of the Other’s desire power. The parent’s phantasmagoric constructions about the cause of cancer of their children were another relevant thing, enabling us to have a better understanding of the parents / children link, and of the child’s place in maternal libidinal economy. Thus, the understanding of somatic symptoms in babies and small children should take into account not only the somatic reality of this physical body, but also the vicissitudes of maternal desire that act through the embodiment of the ghost, denouncing the plastic effect that is active in unconscious process, that is, the embodiment (in the son) of the ghost (maternal).